2016
DOI: 10.1002/mnfr.201500735
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D in adipose tissue in obese rats programmed by early weaning and post diet calcium

Abstract: We propose that in obese rat adipocytes, 1,25(OH)2 D down-regulates VDR, resulting in vitamin D resistance, characterized by higher Cyp27b1/1α-Hydroxylase and adipogenesis. Calcium therapy appears to be an outstanding strategy for weight loss and improving endocrine metabolic disorders that are obesity associated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…Our findings suggest a vitamin D resistance in adipocytes at PN120 that may be associated with the fat accumulation in SL rats. In another obesity model, we also found, in adult rats, higher Cyp27b1 and lower Vdr in the VAT, with higher C/EBPβ and PPARγ expression in the adipose tissue, which could be a key factor in obesogenesis (Nobre et al 2016).…”
Section: Hormones and Adipose Tissue Dysfunctionsupporting
confidence: 57%
See 4 more Smart Citations
“…Our findings suggest a vitamin D resistance in adipocytes at PN120 that may be associated with the fat accumulation in SL rats. In another obesity model, we also found, in adult rats, higher Cyp27b1 and lower Vdr in the VAT, with higher C/EBPβ and PPARγ expression in the adipose tissue, which could be a key factor in obesogenesis (Nobre et al 2016).…”
Section: Hormones and Adipose Tissue Dysfunctionsupporting
confidence: 57%
“…Two mechanisms may help to explain the reduction of fat depots in our study: (1) calcium supplementation increases fecal fat excretion (Denke et al 1993, Shahkhalili et al 2001, Jacobsen et al 2005; (2) calcium supplementation decreased CEBP/β and PPARγ expression, 230:2 two proadipogenic and lipogenic biomarkers, in the VAT of early-weaned rats (Nobre et al 2016). Gonzalez and coworkers (2015) have shown that calcium supplementation in humans reduces postprandial appetite sensation.…”
Section: Effect Of Calcium-enriched Dietmentioning
confidence: 70%
See 3 more Smart Citations